Mutation Screening of the Krüppel-Like Factor 1 Gene Using Single-Strand Conformational Polymorphism in a Cohort of Iranian β-Thalassemia Patients. (February 2015) - Zaker-Kandjani, Behzad; Namdar-Aligoodarzi, Pegah; Azarkeivan, Azita; Najmabadi, Hossein; Banan, Mehdi
Abstract The Krüppel-like factor 1 (KLF1) is an essential erythroid-specific transcription factor. Mutations in the human KLF1 gene have different phenotypic effects, ranging from increased Hb F levels to the disruption of erythropoiesis. Here, we screened 227 Iranian β-thalassemia (β-thal) patients for the presence of KLF1 mutations by using the single-strand conformational polymorphism (SSCP) approach. Our aim was to assess the potential effect of these mutations on the β-thal disease severity. After screening, two variants were found. One patient carried a potentially deleterious variant (Polyphen-2) in exon 2 (p.F182L). Another patient was homozygous for a previously unreported intronic variant (KLF1: c.911 + 84A > G). The patient with the p.F182L variant (KLF1: c.544T > C) had noticeably high Hb A2 levels (7.6%), consistent with the phenotypic effect of several previously characterized KLF1 mutations in the same exonic region. In addition, he had higher platelet counts (1, 069, 000/μL) compared to other patients in the cohort.